Elaboração de um painel Business Intelligence para o setor de compras de uma empresa de Engenharia em Mossoró-RN - Chagas, Biafra Targino (Universidade Federal Rural do Semi-Árido, 2019)
It presents a thematic of case study in a company to get indicatives within the themes and readings that add meaning. The main tool for creating a clear and simple indicator for the purchasing sector of a machine that can really be used in a decision making, with a significant temporary data number and with the same speed. The specific objectives are the extraction, cleaning and agglutination of these data, which means that it has consolidated into an indicator of performance and, therefore, important for the management, as well as an information treatment base for an industry that has levels. the ombreads to all in the language is not founder to all in the language is not found. The methodological search as a qualitative-quantitative research using the KDD method for the treatment and the realization of this data, which finally reveals a real situation that the indicator of purchases made will show the sector of purchases, research, for notes of data and sessions and the importance of the manager in this process.
Monografia
Keywords: Compras; Tomada de decisão; Indicador; KDD; Business intelligence; Shopping; Decision making; Indicator; KDD; Business intelligence; ENGENHARIAS::ENGENHARIA DE PRODUCAO